2012
DOI: 10.3892/ol.2012.614
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression of Treg-associated cytokine IL-35 along with IL-10 and TGF-β in acute myeloid leukemia

Abstract: Abstract. Acute myeloid leukemia (AML) is the most common hematological malignancy in adults, characterized by distorted proliferation and the development of myeloid cells and their precursors in the blood and bone marrow. Interleukin 35 (IL-35), a novel inhibitory cytokine secreted by regulatory T (Treg) cells is a novel potential target used for the therapeutic manipulation of Treg activity in order to treat cancer and autoimmune diseases. To investigate the role and imbalance of Treg-related cytokines in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 40 publications
5
45
1
Order By: Relevance
“…to the severity of the disease [28][29][30]. These findings indicate that inflammatory mediators can induce IL-35 expression in human tissues and indeed this was confirmed by a separate study in which anti-CD3/CD28 were used to stimulate human T regs, and high amounts of soluble IL-35 were induced [31].…”
Section: Discussionsupporting
confidence: 67%
“…to the severity of the disease [28][29][30]. These findings indicate that inflammatory mediators can induce IL-35 expression in human tissues and indeed this was confirmed by a separate study in which anti-CD3/CD28 were used to stimulate human T regs, and high amounts of soluble IL-35 were induced [31].…”
Section: Discussionsupporting
confidence: 67%
“…Also, an increased level of IL-10 in serum after treatment with baicalin was noticed in an animal model of heatstroke [39]. Significantly higher levels of plasma IL-10 were observed in AML patients compared with healthy controls or AML patients in complete remission [40]. Similarly, a higher level of IL-10 was determined in cell culture supernatants from B-ALL and T-ALL patients in comparison to those in the controls [41].…”
Section: Discussionmentioning
confidence: 96%
“…More recently, other IL-35-producing cells have been identified, such as tumor antigen (Ag)-specific CD8 + CTLA-4 + Treg cells [16] and B cells after acquiring suppressive function upon stimulation via TLR4 and CD40 [17]. In addition, several studies have demonstrated IL-35 being expressed in different tumors [15,18,19], whereby it promotes angiogenesis and neoplastic growth by suppressing anti-tumor immunity [20]. Nevertheless, exogenous administration of rIL-35, or its ectopic expression (i.e., in cells normally nonexpressing the cytokine), was found to be protective in pathological conditions such as overwhelming inflammation combined with uncontrolled autoimmune responses, namely CIA [12], experimental autoimmune encephalomyelitis (EAE) [21], autoimmune diabetes [22], inflammatory bowel disease [15,23], atherosclerosis [24] and allergic airway inflammation [25].…”
Section: Introductionmentioning
confidence: 97%